Justification of representative data volume of porosity and permeability properties for obtaining statistically reliable petrophysical connections - Abrosimov Andrei A.; Shelyago Evgenii V.; Yazynina Irena V. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2018)
The article discusses the issues of justifying the data volume for a petrophysical description of an object based on the results of traditional laboratory measurements, as well as X-ray tomography data processing. A new approach to the calculation of porosity and permeability properties of reservoirs with the data of the X-ray tomography method by forming an array of virtual cubes is considered. The issues of required number of allocated cubes for fluid dynamics modeling are discussed. The criteria for the number of laboratory measurements and virtual cubes derived from a digital model for obtaining statistically reliable petrophysical connections are shown. Paper concludes that it is necessary to correctly compare the calculated and laboratory petrophysical connections.
Keywords: rock sample analysis; X-ray tomography; petrophysical connections; data volume; porosity; permeability; virtual cube; method of the reflected waves; kinematic interpretation; velocity model; stacking velocity